Predictors of social intelligence, empathy, and self-efficacy among sexual offenders - Cartwright, Angie D. (Journal of addictions & offender counseling, 2022)
The authors aimed to assess the predictive nature of social intelligence, empathy, general self-efficacy (GSE), time in counseling, and risk-level in a sample of sexual offenders receiving counseling services (n = 151). No mean differences in variables were observed on the basis of victim type, offense type, or risk level. Linear regression models indicated that study variables accounted for 22% of the variance in social intelligence and 13% of the variance in empathy. In both models, GSE emerged as the strongest predictor after accounting for other variables.